The Potential Role of Growth Hormone on the Endometrium in Assisted Reproductive Technology - Liu, Fen-Ting; Wu, Ze; Yan, Jie; Norman, Robert J.; Li, Rong (Frontiers in Endocrinology, 2020)
Growth hormone (GH) has been considered as an adjuvant treatment in human assisted reproductive technology (ART) for several years. Its action was largely attributed to an improvement of ovarian function and less emphasis was paid to its role in the uterus. However, there is increasing evidence that GH and its receptors are expressed and have actions in the endometrium and may play an important role in modifying endometrial receptivity. Thus, in this review, we firstly describe the existence of GH receptors in endometrium and then summarize the effects of GH on the endometrium in clinical situations and the underlying mechanisms of GH in the regulation of endometrial receptivity. Finally, we briefly review the potential risks of GH in ART and consider rationalised use of GH treatment in ART.